Antioxidant properties of pancreatic hydrolysates from various protein sources - Bayarjargal, M; Ariunsaikhan, Ts; Lkhagvamaa, E; Ankhtsetseg, B; Gan-Erdene, T; Regdel, D (Mongolian Journal of Chemistry, 2014)
Antioxidant activity of pancreatic hydrolysates of casein, spent brewer’s yeast, bovine liver and tendon was evaluated in comparison to unhydrolised substrates by ABTS assay. In the result of enzymic treatment ABTS cation radical scavenging activity of spent brewer’s yeast, bovine liver and bovine tendon was increased in 4.8, 3.3, and 2.3 times respectively, except casein. The IC50 values of ABTS cation radical scavenging for casein and it’s hydrolysate were similar. The IC50 values of DPPH radical scavenging activity for pancreatic hydrolysates of casein, spent brewer’s yeast, bovine liver and tendon were 1.8±0.1 mg/ml, 1.3±0.1 mg/ml, 1.7±0.1 mg/ml, and 6.2±0.1 mg/ml respectively. Above mentioned hydrolysates of various origin were produced at the same conditions (temperature 50oC, pH 7.5-8.9, duration 5 hours) using fresh bovine pancreatic tissue as an enzyme source. The extent of hydrolysis expressed as AN/TN (amino nitrogen/total nitrogen) for hydrolysates had values from 0.36±0.02 to 0.46±0.04. DOI: http://doi.dx.org/10.5564/mjc.v15i0.321 Mongolian Journal of Chemistry 15 (41), 2014, p43-46